Cities in civilization: culture, Innovation and urban order - Hall, Peter (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2003)
This paper starts by taking a broad historic view: ranging over 2,500 years of urban history, it distinguishes three different kinds of creativity that have helped shape three very different kinds of city. The first is artistic creativity, as manifested in such classic cases as ancient Athens, Renaissance Florence, or Paris around 1900. The second is scientific and technological creativity, as demonstrated by cities ranging from Manchester in the Industrial Revolution to Silicon Valley today. The third is urban creativity, as evidenced by the ability of cities to tackle their own pressing problems - as in mid-nineteenth-century London or Los Angeles in the 19205 and 1930s. The paper then argues that in the twenty-first century the key will be the marriage of art and technology, which will underpin a whole new range of industries based on creativity. This in turn will support cultural consumption and, through it, tourism. But this will also demand continued urban innovation to produce new kinds of urban quality. The quality of urban life, not material resources, will prove to be a critical factor of production for the new economy. And this leads to a discussion of the development strategy for twenty-first century cities in Ireland.
Keywords: Urban geography -- Ireland